Difference between revisions of "Side Proof 5"

From Polymath1Wiki
Jump to: navigation, search
(Proof)
(Proof)
Line 37: Line 37:
  
 
1) f[485,514] = -7-f(97)+f(127)-f(163)-f(167)+f(251)+f(257)+f(487)+f(491)+f(499)+f(503)+f(509) >= -4
 
1) f[485,514] = -7-f(97)+f(127)-f(163)-f(167)+f(251)+f(257)+f(487)+f(491)+f(499)+f(503)+f(509) >= -4
 +
 
2) f[251,266] = 7+f(127)+f(131)+f(251)+f(257)+f(263) <= 4
 
2) f[251,266] = 7+f(127)+f(131)+f(251)+f(257)+f(263) <= 4
 +
 
3) f[319,336] = -7-f(107)-f(109)+f(163)+f(167)+f(331) >= -4
 
3) f[319,336] = -7-f(107)-f(109)+f(163)+f(167)+f(331) >= -4
 +
 
4) f[207,218] = -5+f(107)+f(109)+f(211) >= -4
 
4) f[207,218] = -5+f(107)+f(109)+f(211) >= -4
  

Revision as of 00:29, 16 June 2015

This page will handle one of the long cases in the Human proof that completely multiplicative sequences have discrepancy greater than 3, so that the page can be shorter and not have so many long sections. Specifically, this page will take care of the case where we assume: f(2)=f(7)=f(19)=f(67)=1, f(23)=-1.

Proof

s(74)=4+f(71)+f(73), so f(71)=f(73)=1.

We have two equations:

1) f[145,154] = -4+f(149)+f(151) >= -4

2) f[295,304] = 5-f(101)+f(149)+f(151) <= 4

Subtracting (2) from (1) we get:

(1)-(2) = -9+f(101) >= -8, so f(101)=1

Updating the table:

0 1 2 3 4 5 6 7 8 9
0|+ + - + - - + + +   0-9
- - - - + + + - + +   10-19
- - - - - + - - + +   20-29
+ - + + - - + + + +   30-39
- - - + - - - + - +   40-49
+ + - - - + + - + -   50-59
+ - - + + + + + - +   60-69
- - + - + - + - + +   70-79
- + - - - + + - - +   80-89
- - - + + - - ? + -   90-99
+ + + ? - + - ? - ?   100-109
+ - + + - + + - - -   110-119
+ + - + - - + ? + -   120-129
+ ? + + + + - ? + ?   130-139

We have four equations:

1) f[485,514] = -7-f(97)+f(127)-f(163)-f(167)+f(251)+f(257)+f(487)+f(491)+f(499)+f(503)+f(509) >= -4

2) f[251,266] = 7+f(127)+f(131)+f(251)+f(257)+f(263) <= 4

3) f[319,336] = -7-f(107)-f(109)+f(163)+f(167)+f(331) >= -4

4) f[207,218] = -5+f(107)+f(109)+f(211) >= -4

Adding them together like this:

(1)-(2)+(3)+(4)+26: -f(97)-f(131)+f(211)-f(263)+f(331)+f(487)+f(491)+f(499)+f(503)+f(509) >= 10

Therefore: f(97)=f(131)=f(263)=-1, f(211)=f(331)=f(487)=f(491)=f(499)=f(503)=f(509)=1.

f[219,232] = 7+f(223)+f(227)+f(229), so f(223)=f(227)=f(229)=-1. f[681,688] = 6-f(137)+f(683), so f(137)=1 and f(683)=-1. f[125,138] = 5+f(127), so f(127)=-1.

We now have two equations:

1) s(138) = 3+f(103)+f(107)+f(109) <= 2 2) f[207,218] = -4+f(107)+f(109) >= -4

(2)-(1)+7: -f(103) >= 1

Therefore, f(103) = -1.

f[411,418] = -5-f(139), so f(139)=-1. f[139,154] = -6+f(149)+f(151), so f(149)=f(151)=1. However, now f[295,302] = 6, which forces the discrepancy above 3.